PENERAPAN PENDEKATAN INVESTIGATIF BERSTRATEGI QUANTUM UNTUK MENINGKATKAN KEMAMPUAN REPRESENTASI MATEMATIS SISWA - Dores, Dede; Sudin, Ali; Maulana, M. (Jurnal Pena Ilmiah, 2017)
Ability of Representation is the process of applying ideas that are poured in symbols to show an understanding of mathematical concepts. The ability of elementary school representation is still low. The investigative approach of quantum strategy allows students to be actively involved because students construct and rediscover the reflected concept. The investigative approach of quantum strategy has a good effect on the ability of mathematical representation of class V students on flat matter. This is evidenced by the study using quasi-experimental methods with pretest-postets control group design that indicates that a quantum-strategy investigative approach improves students' mathematical representation skills including superior student groups, medium, and the lower group. Based on the result of this research, investigative approach of quantum strategy can be used as a solution to improve the mathematical representation ability of elementary school students.Â